Pelatihan dan Pendampingan Penulisan Karya Tulis Ilmiah Bagi Guru - Novri Gazali; Romi Cendra; Leni Apriani; Aluwis Aluwis; Idawati Idawati; Irhas Sawira (Community Education Engagement Journal, 2019)
The activities of the devotion to the community it aims to provide a supply of knowledge and skills to the teachers and students of SMP 4 Tapung Hilir regencies of Kampar Riau Province. The material covered in the training delivery activities of writing of scientific writing paper. This activity was carried out in junior high Country 4 Tapung Hilir regencies of Kampar Riau Province with the number of participants 14 teachers. The results of these activities are the teacher has the ability to write scientific papers especially in research action class (PTK).